Circulating insulin-like factor 3 (INSL3) in healthy and infertile women - Anand-Ivell, Ravinder; Tremellen, Kelton; Dai, Y.; Heng, Kee; Yosida, M.; Knight, P.G.; Ivell, Richard (Oxford University Press, 2013)
Study question: How does insulin-like factor 3 (INSL3) concentration in blood vary across the menstrual cycle in women? Summary answer: INSL3 is secreted by the theca interna cells of growing antral follicles and is phasic in its expression. What is known already: The relaxin-like hormone INSL3 is known to be expressed in follicles of several mammal species, and was recently shown in cows to be specifically secreted into the bloodstream by growing antral follicles, corresponding to follicular waves. In males INSL3 is known to be acutely independent of the hormones of the hypothalamic-pituitary-gonadal axis, suggesting that in women INSL3 might be a novel biomarker for antral follicle recruitment and development. Study design, size, duration: Two cohorts of women were studied. First, 18 healthy women of reproductive age were followed longitudinally for one and a half cycles, with blood sampling and hormone measurement every 2–3 days. A second cohort comprised a crosssectional study of 909 women attending an infertility clinic, with a single blood sample taken at entry, together with other clinical and hormonal parameters. Participants/materials, setting, methods: Blood samples fromboth retrospective cohorts were analyzed for INSL3 using a highly sensitive time-resolved fluorescent immunoassay, and data were analyzed in comparison with other clinical and hormonal parameters. Main result and the role of chance: For young healthy women of reproductive age, we showed a phasic expression of INSL3 corresponding to antral follicle growth in both the follicular and luteal phases of the cycle, which was significantly (P , 0.05) elevated compared with that during menses. For women attending an infertility clinic, those with diagnosed polycystic ovarian syndrome indicated significantly (P , 0.0005) greater circulating INSL3 levels and those with low ovarian reserve showed significantly (P , 0.002) decreased INSL3 values. Limitations, reasons forcaution: Thesewere retrospective studies and the resultswere obtained fromnatural cycles only, with their inherent variability. Wider implications of the findings:We showfor the first time that INSL3 in women does vary across the menstrual cycle, and appears to reflect the number of growing antral follicles recruited within both follicular and luteal phases.